2006
DOI: 10.1295/polymj.pj2005181
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Aniline through Simultaneous Chemical and Electrochemical Routes

Abstract: ABSTRACT:Simultaneous chemical and electrochemical polymerization of aniline was investigated to explore the competition between two polymerization routes. It was found that initial chemical polymerization may significantly affect the electrochemical polymerization; thus, it is possible to control the polymer morphology. By performing the electropolymerization with slow scans, the initial chemical polymerization results in the formation of a nanostructured backbone, which will also affect subsequent electropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
1
19
0
2
Order By: Relevance
“…However, this electrocatalytic activity will affect the electrochemical system even in subsequent cycles. Similar behavior was also detected for simultaneous chemical and electrochemical polymerization of aniline, where the chemical reaction assists the initial polymer growth without needing the initial monomer oxidation on the substrate electrode 42. Note that Ni nanostructures have been partially formed on the carbon nanotube added, and its role is different from graphite powder as a conductive agent, as this issue will be discussed.…”
Section: Resultssupporting
confidence: 56%
“…However, this electrocatalytic activity will affect the electrochemical system even in subsequent cycles. Similar behavior was also detected for simultaneous chemical and electrochemical polymerization of aniline, where the chemical reaction assists the initial polymer growth without needing the initial monomer oxidation on the substrate electrode 42. Note that Ni nanostructures have been partially formed on the carbon nanotube added, and its role is different from graphite powder as a conductive agent, as this issue will be discussed.…”
Section: Resultssupporting
confidence: 56%
“…As a result, many technological applications have been demonstrated, with PANI widely used as a base material in the development of pH sensors, biosensors, rechargeable batteries, supercapacitors, electrochromics, electromagnetic shielding, light emitting devices, photovoltaics, electrostatic discharges, and corrosion‐protecting coatings . Despite the vast bibliography devoted to PANI, new studies focusing on the polymerization process are reported each year …”
Section: Introductionmentioning
confidence: 99%
“…Electrodes are typically functionalized by a chemical or electrochemical route, with the latter being more appropriate for ensuring a higher reproducibility and are also more adequate to create a good electrical contact between the electrode and the deposited [3,4].…”
Section: Introductionmentioning
confidence: 99%